CHALLENGES OF THE LIFE CYCLE EVALUATION IN BRAZILIAN CONSTRUCTIONS - Witicovski, Lilian Cristine; Azevedo, Nathalia Cardoso De; Wosch, Lorena Victória Januário; Tavares, Sergio Fernando; Freitas, Maria do Carmo Duarte; Silva, Alessandro Camargo da (Encontro Latino-americano e Europeu sobre Edificações e Comunidades Sustentáveis (euroELECS), 2023)
The Life Cycle Assessment (LCA) aims to quantify impacts generated during the entire process of a given product, from raw material extraction to final use. This article describes the experience with the LCA software, Athena Impact Estimator for Buildings (I1E4B) and plug-in Tally (non commercial), identifying its potential and its limitations through a case study, quantifying the Global Warming Potential (GWP), throughout the life cycle of a Brazilian house. The case study presents the definition of the project, the description of the software, the insertion of data from the house of the Brazilian Housing Program My House My Life (MCMV) and the qualitative analysis of the main fragilities or potentialities in using international inventory data and software. While the emergence of BlM-based LCA tools offers to help users such as architects, engineers, and contractors who are not LCA practitioners, this research shows that the tools include specific data input biases and methods which impact LCA outcomes. Thus, a more in-depth analysis of the constructive processes by the users is necessary, even if the project is in an initial phase.